Perkembangan Sosial Masyarakat Pada Masa Penjajahan - Lubis, Meisyah Nurliza; Jannah, Nadhirotul; Prastami, Yulia (Faidatuna, 2023)
The development of society during the colonial period experienced many difficulties for the Indonesian people. Where, during the colonial period the Indonesian people were very miserable where at the time of colonization there was colonialism and imperialism led by Europeans in the archipelago. Apart from the Europeans, there were also the Japanese who colonized Indonesia.In historical records, there are several countries that have occupied Indonesia, namely the Netherlands and Japan. These countries have systems or efforts to achieve their goals, such as during the Dutch colonial period the Dutch carried out a monopoly on the spice trade because Indonesia's natural resource wealth was so abundant and also the location of the Indonesian state was on the path of world trade which made European nations are interested in coming to Indonesia. Meanwhile, during the Japanese period, people were made into forced laborers. This forced labor made many Indonesian people sick and even died from malnutrition. Indonesian society is very influential on the social development of its people, with that there are stages of the formation of a society such as 1. There is a group of people 2. Having a permanent residence in an area or place that has a long term 3. With a long period of time it produces a culture such as values, knowledge and mutual understanding of other cultures.This research uses library research, which is useful for analyzing, studying, and finding things related to research. What is known as library research. Library Research is where someone uses the library to find data that will be examined. The purpose of this research is to find out more about the social development of society during the colonial period.